(untitled) (Hungarian Journal of Industry and Chemistry, 2011)
The macro- and micro-geometric properties featuring the boundary surfaces of machine components are important for quality reasons. The comparison of surfaces is needed if the machined surface is to be matched to preset requirements or the same surface can be manufactured with different manufacturing processes or various measurement and surface testing methods are available, or the time variation of the surface is to be assessed. After the comparison, surface deviations must be numerically evaluated in relation to size, shape, position, and surface irregularity. Nowadays, surface irregularity tends to represent not only the unevenness of the surface but also the comparison of the real surface to a favourable microgeometric structure. Information on the actual surface is obtained through perception (optical or mechanical), and the nominal surface can be a mathematical model, a sample, or a previous condition of the surface in the form of any previous perception, or a previously made print of the surface (replica). During comparison, similarities and differences must be evaluated in terms of the key properties of the surface related to the operation of the given component. Comparison based on visual inspection is a suitable and acceptable method for a quick inspection, for identification of the parts of the component, and for detection of significant deviations. A technically more advanced method is image processing. Three dimensional properties of the surfaces can be evaluated with 3D geometric calculation methods and methods developed for surface roughness. The presentation introduces a method for comparing cylinder surfaces of an internal combustion engine and presents an example of the method currently used in automotive engineering applications.